2017
DOI: 10.31227/osf.io/k4sqe
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pengaturan Pola Tanam Meteorologis Sebagai Salah Satu Upaya Optimalisasi Produktivitas Pertanian Di Kawasan Karst Kabupaten Gunungkidul

Abstract: INTISARIPengaturan pola tanam meteorologis sangat penting dilakukan di kawasan karst Kabupaten Gunungkidul mengingat lahan pertanian yang dominan di kawasan tersebut adalah tegalan dan sawah tadah hujan yang sangat tergantung dengan adanya air dari hujan. Penelitian ini bertujuan untuk (1) mengetahui tipe iklim di kawasan karst Kabupaten Gunungkidul dan (2) menyusun pola tanam meteorologis berdasarkan catatan curah hujan yang ada di kawasan karst Kabupaten Gunungkidul. Satu stasiun hujan yang digunakan dalam p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Gunung Sewu karst areais part of the Indonesian Maritime Continent that regulates many determinants of its rain variability, for example, the Asia-Australia monsoon, El Niño-Southern Oscillation (ENSO), eastwest circulations (Zonal/Walker circulation), north-south circulations (Meridional/Hadley Circulation) and some circulations that are heavily influenced by local factors (Hermawan, 2010;Aldrian, Gates, & Widodo, 2007). In Indonesia, the complex climate conditions are attributed to many factors, to which every part of the country shows varying responses (Gutman, Csiszar, & Romanov, 2000;Haylock & McBride, 2001;Boer, 2003;Athoillah, Sibarani, & Doloksaribu, 2017). Other studies have confirmed that southern Indonesia, including the Gunung Sewu Karst Area, is inclined to have higher rainfall variability than the northern side (Juaeni, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Gunung Sewu karst areais part of the Indonesian Maritime Continent that regulates many determinants of its rain variability, for example, the Asia-Australia monsoon, El Niño-Southern Oscillation (ENSO), eastwest circulations (Zonal/Walker circulation), north-south circulations (Meridional/Hadley Circulation) and some circulations that are heavily influenced by local factors (Hermawan, 2010;Aldrian, Gates, & Widodo, 2007). In Indonesia, the complex climate conditions are attributed to many factors, to which every part of the country shows varying responses (Gutman, Csiszar, & Romanov, 2000;Haylock & McBride, 2001;Boer, 2003;Athoillah, Sibarani, & Doloksaribu, 2017). Other studies have confirmed that southern Indonesia, including the Gunung Sewu Karst Area, is inclined to have higher rainfall variability than the northern side (Juaeni, 2006).…”
Section: Introductionmentioning
confidence: 99%